Praktikum Biologi Selama Pembelajaran Online : Minat Mahasiswa dan Pengaruhnya terhadap Keterampilan Proses Sains - I Putu Artayasa; Dea Marlina; Dita Anggraini Safitri Sipayung; Fitriatunisyah Fitriatunisyah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The application of online learning during the Covid-19 pandemic has an impact on the model of implementing the practicum according to online learning. This study aims to determine student interest in online biology practicum, as well as student perceptions of the effect of online practicum on improving science process skills. The research was conducted on students of the Biology Education Study Program, FKIP, Mataram University. The research sample was taken by convenience sampling technique. The number of samples for this study were 40 6th semester students from classes A, B, C, and D, in the 2020/2021 academic year. This type of research is descriptive research with a quantitative approach using survey methods. Data collection uses a questionnaire distributed online via Google Form. The results showed that students' interest in online practicums was seen from the aspect of interest in the implementation of online practicums as well as motivation and enthusiasm for participating in online practicums including the strong category, but students had a weak preference for online practicums compared to offline practicums. Student perceptions of the effect of online practicum on improving science process skills in the medium category. Thus, online practicums that are strengthened by monitoring and evaluating implementation can be a solution to the implementation of biology practicums during the Covid-19 pandemic.